ENSURING SUSTAINABLE DEVELOPMENT OF TOURISM THROUGH THE FORMATION OF TOURISM CLUSTERS - Muhammedrizayevna, Tairova Mavluda; Djumanazarovna, Xasanova Gulruh; Bayazovna, Giyazova Nozima; O’tkir qizi, Murotova Nigina (International Journal of Psychosocial Rehabilitation, 2020)
The article highlights the objective need to develop tourism, one of the strategic sectors of the economy. The importance, specific features and advantages of using a cluster mechanism to increase the competitiveness of the economy are highlighted. The use of a cluster mechanism is also based on ensuring the competitiveness of tourism products and services. The organization of tourism clusters in the region, their stages and factors influencing them are analyzed, the tasks performed by clusters of tourism activities are presented. There are proposals for the organization and development of tourism clusters.